Yes Logo Uncovering the Recipes of Branding Success in the World’s Largest Consumer Market - Wang, Jiazhuo George; Qin, Shuo; Wang, Allison (Springer Nature Singapore : Imprint: Springer, 2023)
XV, 207 p. 14 illus., 12 illus. in color.